(untitled) (Lectio: Journal of Language and Language Teaching, 2025)
This study aimed to identify whether the use of cartoon images can assist eighth-grade students at SMP N 5 Kota Kupang in improving their speaking abilities. The descriptive method was used to characterize speaking skills. This study employed a test for describing cartoon picture series. This study focused on three distinct components of speaking: grammar, vocabulary, and pronunciation. According to the analysis’s findings, the researcher discovered that (1) eighth-grade students were able speak English, particularly when describing cartoon picture series orally. (2) Students in the eighth grade showed ‘very good’ speaking ability level (15.6). The students’ speaking ability level for each element is as follows: Grammar has a score of 104, while the average is 5.2, and vocabulary has a score of 108, while the average is 5.4. The average score for pronunciation is 5, while the total score is 100. The researcher provides some recommendations based on the results of the research. The first is recommended for the English teachers to train students to speak English in front of the class while presenting something, such as a picture or other learning media, and encourage them to read more in order to improve their literacy skill. Secondly, the students need to work on their pronunciation by listening to English-language radios, music, and television shows. The future researchers are encouraged to conduct the similar research with different media and strategies in improving the language learners’ speaking ability.